The Effect of Cantilevers on Interior Lighting: Case of Denizli Merkezefendi Library - Akif Ayberk Çetin; Şule Yılmaz Erten (Livenarch+ Journal)
Libraries are buildings where important sources of information are located, serving to make information accessible, to encourage access to information and to increase the general level of knowledge of the society. In the design of these spaces where users spend long hours for research, reading and study, adequate and qualified lighting is a very important and important issue in terms of reader comfort and protection of books. In modern library buildings, in individual, group and collective study areas with rich space options, the lighting of the spaces according to the nature of the study plays a supporting role in visual comfort and function. On the other hand, the correct use of light can sometimes be interrupted by some mass facade movements that increase the aesthetic appearance in the design of architectural structures, and may negatively affect the visual comfort in the building. In this study, the effect of aesthetic and functional façade movements on natural lighting in buildings is investigated. In the field study part of the study, Denizli Merkezefendi Municipality Central Library, one of the examples of modern library buildings, is discussed. As a study methodology, literature research on natural and artificial lighting design in libraries was conducted, and lighting criteria in buildings were analyzed. Dialux program was used for data analysis and lighting simulation of the building. As a result of the examinations made on this model, the natural lighting effects in the building were analyzed through Denizli Merkezefendi Municipality Central Library and recommendations were made. In the conclusion part of the study, it is shown that cantilever masses can have direct and indirect negative effects on providing the required illumination level for the function in the interior space in terms of the determined criteria.